Functionalization of Titanium Dioxide Nanoparticles in Anatase-Rutile Phases and Quartz Crystal Microbalance for Humidity Sensing Materials - Mardiana, Laili; Fajriah, Baiq Nurul; Wirawan, Rahadi; Alaydrus, Alfina Taurida; Rahayu, Susi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
A QCM (Quartz Crystal Microbalance) can be developed as a humidity sensor with a selective coating material. TiO2 (titanium dioxide) is a metal oxide with several crystal phases: anatase and rutile phases. However, there are few studies on the crystal phase investigation of a TiO2-based humidity sensor. Thus, this study aimed to develop a humidity sensor by functionalizing TiO2 particles with different crystal phases. The coating materials were prepared by ultrasonication. The synthesis was conducted by mixing 7 mL of TTIP (Titanium (IV) Isopropoxide) precursor in ethanol. This solution was stirred for 30 minutes, ultrasonicated, and heated for 16 hours to make a gel. The next step was a calcination process with two different temperatures to produce different crystal phases: 500oC (anatase) and 700oC (rutile). The synthesized powders were analyzed using XRD-SEM and coated onto the surfaces of the QCMs used as the developed sensors. These sensors were tested inside a chamber using a humidity control kit and a frequency counter (humidity levels: 57% to 92%). The results show that the rutile phase has a smaller particle diameter (252.672 nm) than the anatase phase (384.589 nm). The humidity sensing examinations indicate that the anatase-phase sensor has faster response-recovery times (19 seconds and 8 seconds) than the rutile-phase sensor (28 seconds and 50 seconds). It can be concluded that TiO2 particles in the anatase and rutile phases can be functionalized as a high-sensitivity coating material for a QCM humidity sensor.